(untitled) (Revista Electrónica Calidad en la Educación Superior, 2021)
This article is aimed at determining the factors that affect the academic lag and dropout of the student population from the formation programs of elementary education career at the Universidad de Costa Rica, Rodrigo Facio’s campus. Within the framework of a quantitative research with a descriptive scope, a questionnaire was applied to 17 students in a condition of academic lag or alert. The results suggest some factors for which they drop out or postpone their studies, factors that are mainly related to family and socioeconomic reasons. As part of the implications of the study for quality management, actions are proposed for the attention and monitoring of this population.